World Economy Winter 2015 - Stubborn weakness in the world economy - Klaus-Jürgen Gern; Philipp Hauber; Nils Jannsen; Stefan Kooths; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW), 2015)
Global growth slowed in 2015. While we forecast the world economy to gradually gain momentum over the coming two years, the upturn is expected to be slow. PPP-weighted global GDP is expected to increase by 3.1 per cent this year followed by 3.4 and 3.8 per cent in 2016 and 2017, respectively. Thus we have reduced our September forecast for 2015 and 2016 by a quarter of a percentage point, whereas the outlook for 2017 has improved slightly. The expansion in advanced economies continues to strengthen gradually as accommodative monetary policies, a pick-up in wages and higher real incomes due to cheaper oil will boost private consumption and investment against the background of improved financial balances in the private sector. In emerging economies, lower commodity prices and structural problems will continue to weigh on growth, although we expect growth in this group of countries to pick up somewhat over the forecast horizon. – – Die Weltwirtschaft expandierte im Jahr 2015 verlangsamt. Sie wird sich in den kommenden beiden Jahren zwar allmählich beleben, aber vorerst nur wenig Schwung entwickeln. Der Anstieg der Weltproduktion gerechnet auf Basis von Kaufkraftparitäten wird sich von 3,1 Prozent in diesem Jahr auf 3,4 Prozent bzw. 3,8 Prozent in den Jahren 2016 und 2017 erhöhen. Damit haben wir unsere Prognose vom September für 2015 und 2016 um jeweils rund einen Viertel Prozentpunkt gesenkt, während wir die Zuwachsrate für 2017 leicht angehoben haben. Der Aufschwung in den fortgeschrittenen Volkswirtschaften wird sich in leicht verstärktem Tempo fortsetzen. Eine insgesamt weiter expansive Geldpolitik, allmählich anziehende Löhne und (zunächst noch) Anregungen vonseiten des Ölpreises fallen angesichts fortschreitender Entschuldungsprozesse im privaten Sektor zunehmend auf fruchtbaren Boden. Die Expansion in den Schwellenländern wird vorerst weiter durch niedrige Rohstoffpreise und strukturelle Probleme gedämpft, die Konjunktur in dieser Ländergruppe dürfte sich im Prognosezeitraum gleichwohl allmählich beleben.
Keywords: 330; advanced economies; emerging economies; firm indebtedness; monetary policy; Japan; Russia; ASEAN